MIGRASI FORMALDEHID PADA AIR MINUM DALAM KEMASAN (AMDK) - Satria Heriady; Sofia Anita; Syafruddin Nasution (Program Pascasarjana Universitas Riau, 2015)
Polyethylene terephtalate (PET) is used in bottled drinking water. However, PET canbe easily damaged by the effect of temperature and storage time. Formaldehydemigrates from PET as a thermal degradation product. The aim of this research is todetermine the levels of formaldehyde in bottled drinking water based on length time andtemperature and the result were compared with KEPMENKES the Republic ofIndonesia Number 907/MENKES/SK/VII/2002 and Environment Protection Agency(EPA) year 2012. UV-Vis spectrophotometer is used to measure the levels offormaldehyde in the sample and Schiff’s reagent was added to the samples to detect thepresen of formaldehyde. The result of this research showed that the migration offormaldehyde into the drinking water were fluctiative. The highest concentration offormaldehyde was in SPA water 0,214 mg/L at 60°C during 2 weeks storage and 0,155mg/L at 37°C for AQUA during 3 weeks storage. Formaldehyde content of both sampleSPA and AQUA were below the treshold based on KEPMENKES the Republic ofIndonesia Number 907/MENKES/SK/VII/2002 of these Terms and Monitoring ofDrinking Water Quality and Environment Protection Agency (EPA) year 2012.